Energy Harvesting and Storage by Water Infiltration of Eggshell Membrane. Issue 3 (14th January 2020) - Gao, Dan; Liu, Changhong; Fan, Shoushan
Abstract : As a domestic waste in daily life, eggshell membrane (ESM) is a unique biomaterial due to its biocompatibility, bioadsorption, and the structure of interwoven and coalescing fibers with many pores which can be utilized in many fields. Herein, a new kind of potentially biocompatible energy harvesting and storage device based on polymer polyaniline/carbon nanotube (PANI/CNT) composite electrodes and ESM is designed. Without external electric power, a single device can extract a maximal output voltage of 0.26 V from water osmosis. The energy can be stored directly and released circularly, and the output voltage can achieve superposition by integrating devices in series. This self‐charging bioelectric phenomenon can be explained by the membrane potential of the ESM induced by water movement. Due to the biocompatible feature of the ESM, and sufficiently high electric output, this study provides a new idea for sustainable and biocompatible energy harvesting and storage devices. Abstract : While harvesting the electrical energy from the osmosis of liquid to the eggshell membrane, the energy can be stored directly and the device can achieve discharging and recovering circularly. Sufficiently high electric output up to 0.26 V can be achieved by a single unsealed device. These devices are promising as an ideal power supply to medical implant devices.